2020
DOI: 10.3390/s20030645
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Positioning and Orientation of MLSS in a Subway Tunnel Based on Sparse Point-Assisted DR

Abstract: When performing the inspection of subway tunnels, there is an immense amount of data to be collected and the time available for inspection is short; however, the requirement for inspection accuracy is high. In this study, a mobile laser scanning system (MLSS) was used for the inspection of subway tunnels, and the key technology of the positioning and orientation system (POS) was investigated. We utilized the inertial measurement unit (IMU) and the odometer as the core sensors of the POS. The initial attitude o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Li et al [12], Wang et al [13] uses INS/odometer integrated DR to calculate the position and attitude of MLS in underground space, which uses laser scanner to survey the control points along the track and then correct the pose error by assuming that it is distributed according to polynomials. Their studies have the same disadvantages: the position error is only corrected near the control points, and the overall error of the solution is not corrected from the internal law of DR, resulting in the uncorrected attitude error, and without considering the possible gross errors of some control point coordinates, finally only the absolute surveying accuracy of sub centimeter level can be achieved.…”
Section: Research Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al [12], Wang et al [13] uses INS/odometer integrated DR to calculate the position and attitude of MLS in underground space, which uses laser scanner to survey the control points along the track and then correct the pose error by assuming that it is distributed according to polynomials. Their studies have the same disadvantages: the position error is only corrected near the control points, and the overall error of the solution is not corrected from the internal law of DR, resulting in the uncorrected attitude error, and without considering the possible gross errors of some control point coordinates, finally only the absolute surveying accuracy of sub centimeter level can be achieved.…”
Section: Research Statusmentioning
confidence: 99%
“…x is the track and y is the CPIII control point. The relative accuracy between CPIII control points is better than 1 mm [13]. Therefore, CPIII control network is suitable for been used as the external reference to correct the error of INS/ odometer integrated navigation from the perspective of 'scale' and 'shape'.…”
Section: Relationship Between Control Points and Surveying Equipmentmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these is, of course, laser scanning. As presented in [ 25 ] by Qian Wang, et al, a mobile laser scanning system (MLSS) was used for the inspection of subway tunnels, and the key technology of the positioning and orientation system (POS) was investigated. The authors obtained an “accuracy of the 3D coordinates of the point clouds of 8 mm, and the experiment also showed that it takes less than 4 h to complete all the inspection work for a 5–6 km long tunnel.” The missing of the very practical GNSS technology for accurate positioning in tunnels or radio-obscured spaces must be replaced by laser scanning, ultrasonic scanning, methods that must be also completed with map matching (MM), intermittent responders, coordinates of control points, and so forth [ 26 ].…”
Section: Related Workmentioning
confidence: 99%
“…Based on mobile laser scanning technology, many scholars at home and abroad have designed building information models (BIMs) to develop deformation monitoring systems for tunnels or other retaining structures [10,11]. At the same time, 3D laser scanning technology can not only design the structural positioning and orientation system [12][13][14][15][16][17] but also create a 3D building information model (BIM) [18,19] based on the orientation system. In fact, by optimizing the deformation data extraction and improving the registration algorithm [20][21][22][23], the accuracy of tunnel 3D modeling and deformation monitoring can be efectively improved [14,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%